Paradoksy awangardowego zaangażowania. Milczenie artysty i rewolucja. Przypadek Aleksandra Wata - Kmiecik, Michalina (Zagadnienia Rodzajów Literackich, 2019)
At the end of the 1920s Aleksander Wat quits publishing his literary texts and focuses on editorial and journalistic activity thus developing the model of a romantic "rigorist of action" created by Adam Mickiewicz. The purpose of this article is, first of all, to compare the ideological postulates of Mickiewicz and Wat regarding the relationship between language and action, as well as to demonstrate the convergence of their social and political background. Secondly — I will examine the journalistic activity of Wat from the period of “Miesięcznik Literacki” (1929–1930): analyze his critique of Futurism (as too “literary” and only apparently engaged) and a new formula of non-fiction (presented in essays devoted to the social role of reportage).